Total phenolic and flavonoid content and antioxidant activity of aqueous and methanol extracts of Viscum album L. aerial parts - Kočović, Aleksandar; Bradić, Jovana; Petrović, Anica; Tomović, Marina; Popović-Milenković, Marija; Uštević, Andjela; Milovanović, Olivera; Andjić, Marijana (Archives of Pharmacy, 2022)
Mistletoe, Viscum album L. has been used in traditional medicine for different treatments. The aim was to determine the total phenolic and flavonoid content in aqueous and methanol extracts of the dry aerial parts of this plant collected during flowering stage and to examine their antioxidant activity. Extraction of plant material was performed by refluxing using distilled water and methanol as solvents, and plant to solvent ratio was 1:10. Before extraction, plant material was grounded and sieved. After procedure, extracts were filtered and solvents were evaporated under vacuum. Obtained dry extracts were used for further investigations. DPPH (1,1-diphenyl-2-picrylhydrazyl) test was used to determine the antioxidant activity. Total phenols and flavonoids were determined spectrophotometrically using Folin–Ciocalteu reagent for phenols and AlCl3 reagent for flavonoids. Antioxidant activity was expressed as IC50 values, which represent the concentration of the tested sample that inhibited 50% of the DPPH radicals. The IC50 value of aqueous extract was 1334.42±1.22 μg/ml, while for the methanol extract was 1132.48±1.34 μg/ml. For ascorbic acid, the IC50 value was 33.54±2.12 μg/ml. The total phenolic content of aqueous extract was 164.65±6.42 mg GAE/g, and the total flavonoid content was 75.53±2.21 mg QE (quercetin equivalent)/g. The total phenolic content of the methanol extract was 179.27±16.04 mg GAE/g, and total flavonoid content was 79.71±3.42 mg QE/g. The methanol extract of the aerial parts of the V. album plant had a higher content of total phenols and flavonoids than the aqueous extract. Also, methanol extract showed better antioxidant activity than aqueous extract.